Urgency of Managing Digitalization in Higher Education - Susanti Saragih; Jann Hidajat Tjakraatmadja; Andika Putra Pratama (Research Synergy Foundation, 2023)
The digital transformation of higher education institutions has become one of the most significant trends in recent years. Unfortunately, this change is facing many challenges and pitfalls. Therefore, understanding how to manage digitalization amid continuous change should be a top priority for leaders of higher education institutions. This article reviews previous research focused on digitalization in higher education. Using non-systematic literature methods, it starts by summarizing the main driving forces, barriers, and pitfalls of digitalization in higher education. The selected papers were chosen based on their relevance to the article's purpose. The findings discuss the four main elements of managing digitalization in higher education. These four elements should be a priority in universities' strategy. Finally, the proposed framework in this article is expected to contribute to developing theory and practice in managing digitalization in higher education.